Lowest unoccupied molecular orbital managing function of CN-substituted dibenzofuran in high triplet energy hosts for blue thermally-activated delayed fluorescence organic light-emitting diodes. Issue 42 (14th October 2021) - Byeon, Sung Yong; Lee, Kyung Hyung; Lee, Jun Yeob
Abstract : The effect of lowest unoccupied molecular orbital management of high triplet energy electron transport type hosts in organic light-emitting diodes was investigated by synthesizing three hosts derived from CN-modified dibenzofuran. Abstract : The effect of lowest unoccupied molecular orbital (LUMO) management of high triplet energy electron transport type hosts on the device performance of blue thermally-activated delayed fluorescence (TADF) organic light-emitting diodes was investigated by synthesizing three hosts derived from 3, 6-dicyanocarbazole, CN-modified dibenzofuran, and benzonitrile. The three host materials were designed to share a highly twisted molecular structure and high triplet energy above 3.0 eV with different LUMO distributions by controlling the CN substituents in the dibenzofuran unit. A wide LUMO distribution due to the CN substituents improved the electron transport properties of the hosts. The host materials were applied as electron transport type hosts in a mixed host system with a hole transport type host of 3, 3′-di(9 H -carbazol-9-yl)-1, 1′-biphenyl. Among the hosts, the electron transport type host with two CN-substituted hosts demonstrated a high EQE of 19.3% and about a 60% improved device lifetime in the blue TADF devices due to the wide LUMO dispersion.